2020
DOI: 10.1039/d0ta07289c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired roll-to-roll solar-thermal energy harvesting within form-stable flexible composite phase change materials

Abstract: Converting solar energy into storable thermal energy within organic phase change materials has emerged as a promising way to overcome solar intermittency and continuously harness solar-thermal energy for many heating-related...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…Apart from commercial MF, PU foam is also utilized to encapsulate PCMs for preparing flexible composite PCMs. Flexible solar-absorbing composite PCMs were prepared by impregnating stearic acid (SA) into rGO-coated PU foam ( Chang et al., 2020 ). Inspired by the behavioral spreading and folding of buttery wings, this roll-to-roll charging strategy overcame the heat transfer limitation for fast solar-thermal energy harvesting within flexible composite PCMs.…”
Section: Advanced Flexible Composite Pcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from commercial MF, PU foam is also utilized to encapsulate PCMs for preparing flexible composite PCMs. Flexible solar-absorbing composite PCMs were prepared by impregnating stearic acid (SA) into rGO-coated PU foam ( Chang et al., 2020 ). Inspired by the behavioral spreading and folding of buttery wings, this roll-to-roll charging strategy overcame the heat transfer limitation for fast solar-thermal energy harvesting within flexible composite PCMs.…”
Section: Advanced Flexible Composite Pcmsmentioning
confidence: 99%
“…However, an insightful understanding of flexible engineering of advanced PCMs is still insufficient. From the perspective of material science, herein, we systematically outline a comprehensive review of flexible PCMs based on different dimensional flexible additives, including 1D flexible additives, such as cellulose( Wei et al., 2019 ) and carbon nanotubes (CNTs) ( Wang et al., 2021a ); 2D flexible additives, such as graphene and their derivatives( Li et al., 2018 ), boron nitride (BN) ( Wang et al., 2020a ) ( Yang et al., 2018 )and MXene( Gong et al., 2021 ); and 3D flexible additives, such as EG( Wu et al., 2020c ), foam( Chang et al., 2020 ) and other 3D flexible materials 157 ( Figure 1 ). Moreover, we highlight fabrication techniques, flexibility evaluation strategies, advanced applications, current developments and further perspectives for flexible composite PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, HTFs (e.g., metal oxide, and carbon materials) were widely used due to their excellent thermal conductivity and black color nature. [227][228][229][230] Considering the requirements for heat transfer fluids in the thermal management process, [226,231,232] the properties of PLs may meet this demand. For example, a previous study has indicated that hollow carbon PLs can be exploited as a promising platform for heat energy transfer.…”
Section: Thermal Managementmentioning
confidence: 99%
“…For example, Chang et al used rGO as a photothermal conversion medium, which enabled the photothermal conversion capacity of composite PCM up to 94.0%. 32 RHTC has a wider range of visible light absorption, and thus more thorough absorption of light, which can convert light energy into heat energy more effectively. It can make up for the disadvantage of poor photothermal conversion of BN and give the composite PCM excellent photothermal conversion ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Carbon-based materials have a high photothermal conversion capacity due to their inherent advantages. For example, Chang et al used rGO as a photothermal conversion medium, which enabled the photothermal conversion capacity of composite PCM up to 94.0% . RHTC has a wider range of visible light absorption, and thus more thorough absorption of light, which can convert light energy into heat energy more effectively.…”
Section: Introductionmentioning
confidence: 99%